O Instituto do refúgio e suas assimetrias: um estudo sobre a perseguição relacionada ao gênero - Barretti, Kathleen de Almeida (2022)
This research sought to address the issue of determining the refugee status of women who have suffered gender-related persecution. It also sought to define the main international and regional mechanisms for the protection of refugees and mapped how the determination of refugee status is carried out in Brazil. In a second moment, this dissertation analyzed some academic movements that deal with the theme. Finally, through interviews, an in-depth case study was conducted on the Brazilian reality of determining the refugee status of women who have suffered gender-related persecution. The interviews were conducted with employees of institutions that work with the refugee theme in Brazil. With these interviews, the researcher was able to map the main problems and advances regarding the protection of refugee women in the country, as well as public policies on the subject